Effectivenes of hepatitis B vaccination in STIKes Jenderal Achmad Yani Cimahi students - Gina Khairinisa; Fini Ainun Qolbi Wasdili (Medical Laboratory Analysis and Sciences Journal, 2019)
Hepatitis B is an inflammatory disease of the liver caused due to an infection from the hepatitis B virus (HBV). This inflammatory liver disease can become chronic, causing liver cirrhosis, and then become cancerous. Hepatitis B vaccination process by injection. Hepatitis B antibodies can appear in response to Hepatitis B vaccination. The purpose of this study as an effort to decide the effectiveness of Hepatitis B vaccination by seeing whether active immunity has formed against infections caused by the Hepatitis B virus to Stikes Student Jenderal Ahmad Yani Cimahi. The research method used in this research is descriptive. Samples used in the study were 30 people who met the inclusion criteria. From the results of studies using the immunochromatographic method, all positive samples were found with hepatitis B antibodies. Based on the research can be concluded that the vaccination conducted on Stikes Jenderal Achmad Yani Cimahi has given effective results and has a protective titer to prevent hepatitis B virus infection that will attack his body.